Mercury-arsenic sulfosalts from the Apuan Alps (Tuscany, Italy). II. Arsiccioite, AgHg2TlAs2S6, a new mineral from the Monte Arsiccio mine: occurrence, crystal structure and crystal chemistry of the routhierite isotypic series. (February 2014) - Biagioni, C.; Bonaccorsi, E.; Moëlo, Y.; Orlandi, P.; Bindi, L.; D'Orazio, M.; Vezzoni, S.
Abstract: The new mineral species arsiccioite, AgHg2 TlAs2 S6, was discovered in the baryte-pyrite-iron oxide ore deposit exploited at the Monte Arsiccio mine, near Sant'Anna di Stazzema (Apuan Alps, Tuscany, Italy). It occurs as anhedral grains scattered in microcrystalline baryte, associated with cinnabar, laffittite, protochabournéite, pyrite, realgar, Hg-bearing sphalerite and stibnite. Arsiccioite is red, with a metallic to sub-metallic lustre. Minimum and maximum reflectance data for COM wavelengths in air are [λ (nm): R (%)]: 471.1: 29.0/29.4; 548.3: 27.6/28.3; 586.6: 26.1/26.5; 652.3: 24.2/24.6. Electron microprobe analyses give (wt.%): Cu 0.78(6), Ag 8.68(21), Zn 0.47(27), Fe 0.04(1), Hg 35.36(87), Cd 0.20(5), Tl 18.79(33), As 10.77(19), Sb 4.75(10), S 18.08(21), Se 0.07(5), total 97.99(44). On the basis of Σ Me = 6 a.p.f.u., the chemical formula is Ag0.87(2) Cu0.13(1) Zn0.08(4) Fe0.01(1) Hg1.91(5) Cd0.02(1) Tl1.00(2) (As1.56(2) Sb0.42(1) )S1.98 S6.12(6) Se0.01(1) . Arsiccioite is tetragonal, I 2 m, with a 10.1386(6), c 11.3441(5) Å, V 1166.1(2) Å3, Z = 4. The main diffraction lines of the powder diagram are [ d (in Å), visually estimated intensity, hkl ]: 4.195, m, 211; 3.542, m, 103; 3.025, vs, 222; 2.636, m, 114; 2.518, s, 400 and 303. The crystal structure of arsiccioite has been refined by single-crystal X-ray data to a final R 1 = 0.030, on the basis of 893 observed reflections. It shows a three dimensional framework of (Hg, Ag)- centred tetrahedra (1 M 1 + 2 M 2), with channels parallel to [001] hosting TlS6 and (As, Sb)S3 disymmetric polyhedra. Arsiccioite is derived from its isotype routhierite M 1 Cu M 2 Hg2 TlAs2 S6 through the double heterovalent substitution M 1 Cu + + M 2 Hg 2+ → M 1 Hg 2+ + M 2 Ag + . This substitution obeys a steric constraint, with Ag +, the largest cation relative to Hg 2+ and Cu +, entering the largest M 2 site. The ideal crystal chemical formula of arsiccioite is M 1 Hg M 2 (Hg0.5 Ag0.5 )2 TlAs2 S6 . The crystal chemistry of the routhierite isotypic series is discussed. Finally, the distribution of Hg ore minerals in the Apuan Alps is reviewed.